Investigation of structure and properties of melt-spun NiTi based shape memory alloys - Hau, Kieu Xuan; Yen, Nguyen Hai; Ngoc, Nguyen Huy; Anh, Truong Viet; Thanh, Pham Thi; Toan, Nguyen Van; Thanh, Tran Dang; Dan, Nugyen Huy (Vietnam Journal of Science and Technology, 2022)
In this work, we investigated the structure, mechanical properties and corrosion resistance of Ti50Ni50 and Ti16.667Zr16.667A16.667Ni25Cu25 (A = Hf, Nb, Co, Cr and Ga) shape memory alloys (SMAs) fabricated by using melt-spinning method. X-ray diffraction (XRD) and scanning electron microscopy (SEM) analyses reveal that the alloy ribbons are partially crystallized with B19' martensitic structure in the added alloys. The crystalline phase formation and the atomic size difference (δ = 4.33 - 10.25%) significantly affect the hardness, tensile strength, tensile strain, elastic modulus and corrosion resistance of the alloys. The hardness of the alloy gradually increases from 583 HV to 873 HV when adding elements in the order of Hf, Nb, Co, Cr and Ga. Tensile strength, tensile strain and elastic modulus simultaneously reach their maximum of 669.2 MPa, 0.899% and 28.82 GPa, respectively, when Hf is added to the alloy. Ga enhances the corrosion resistance of the alloy ribbons more than other additional elements.